GDF3 Protects Mice against Sepsis-Induced Acute Lung Injury by Suppression of Macrophage Pyroptosis - Jiaxi Lei; Lu Wang; Lijuan Zou; Huijuan Wang; Yunlong Zhang; Shiping Liu; Mingliang Pan; Xue Zhu; Liying Zhan (MDPI AG, 2024)
Sepsis-induced ALI is marked by physiological, pathological, and biochemical irregularities caused by infection. Growth differentiation factor 3 (GDF3) is closely associated with the inflammatory response. Accumulating evidence has demonstrated a close relationship between GDF3 expression and the severity and prognosis of sepsis. However, the precise mechanism by which GDF3 protects against ALI induced by sepsis is still unclear. Following the intravenous administration of GDF3 in this research, we noted a rise in the survival rate, a decrease in the severity of histopathological damage as evaluated through HE staining, a decline in the count of inflammatory cells in bronchoalveolar lavage fluid (BALF), a reduction in the ratio of lung wet/dry (W/D) weight, and a noteworthy decrease in the levels of pro-inflammatory cytokines in both serum and BALF when compared to septic mice who underwent cecal ligation and puncture (CLP). These collective findings unequivocally indicate the protective effects of GDF3 against sepsis-induced ALI. In addition, the GDF3 group showed a significant reduction in the mRNA expression of Caspase-1 and NLRP3 when compared to the CLP group. Following this, we performed in vitro tests to confirm these discoveries and obtained comparable outcomes, wherein the administration of GDF3 notably decreased the levels of Caspase-1 and NLRP3 mRNA and protein in macrophages in comparison to the LPS group. Furthermore, GDF3 exhibited the capacity to reduce the secretion of inflammatory molecules from macrophages. By illuminating the mechanism by which GDF 3 regulates macrophages, this offers a theoretical basis for preventing and treating sepsis-induced ALI.